Yaya niya, nanay ko - Remigio, Ma Corazon; Lim, Nicole; Borromeo, Michelle Parazo (Makati City UNICEF, 2015)
"How does a girl feel growing up in the care of her grandmother, while her mother works as nanny to another little girl?"--Page 4 of cover.
"Unite for children."
"Unang limbag ng unang edisyon, 2002."
"Recommended for children ages 3 and above."
"In English & Filipino text!"
Keywords: Children's stories, Philippine (English)